Frequency of Cardiac Events in Patients with or without Diabetes Admitted to a Cardiac Unit of Dubai Hospital before, during, and after Ramadan - Rashid, Fauzia; Yaseen, Noha; Mahmud, Mirza Saima; Alawadi, Fatheya; Zidan, Marwan; Zaky, Hossam Abdelaziz; Hassanein, Mohamed (Journal of Diabetes and Endocrine Practice, 2025)
Objective To understand the impact of Ramadan fasting on people with diabetes and cardiovascular diseases (CVDs). Many people with diabetes have a range of CVD conditions, such as coronary artery disease, heart failure, and/or diabetic cardiomyopathy. This is of particular importance as there is no benchmark to compare the incidence for cardiac events during fasting in Ramadan in people with diabetes due to lack of adequate studies.Methods We observed the frequency of admission with cardiac events such as congestive cardiac failure, unstable angina, acute coronary syndrome, non-ST elevation myocardial infarction, and ST elevation myocardial infarction in people with and without diabetes across the 3 months of Sha'ban (the month pre-Ramadan), Ramadan, and Shawwal (the month post-Ramadan) in the year 2018. The detailed history and biophysical and biochemical data are presented as frequency and percentages.Result The majority of admissions were from people with Muslim background (87.1%). People with diabetes constituted 45.5% of total admissions. Nondiabetic patients were younger (53.50 ± 11.91 vs. 63.56 ± 13.17 years, p = 0.05) and have significantly higher low-density lipoprotein-cholesterol value compared to those with diabetes (129.70 ± 45.47 vs. 97.00 ± 29.56 mg/dL, p = 0.05). In Muslim patients, hospitalization in the month of Ramadan was much lower compared to the months of Sha'ban and Shawwal (24.1, 40.4, and 35.5%, respectively). Admissions in those with no previous history of diabetes was lower during Ramadan (57.1%) compared to Shaaban (64.6%) and Shawwal (72.2%). In people with diabetes, the hospitalization rate during Ramadan with ischemic heart disease (IHD) was higher (88.91%) compared to the months of Shaaban (63.6%) and Shawwal (62.9.%). However, during the same period, admissions with congestive heart failure (CHF) were much lower (11.1, 36.4, and 36.1%, respectively).Conclusion The overall admission with CVD during Ramadan is lower than the month before or after. The rate of reduction in admissions during Ramadan was marginal in those with previous history of CVD and diabetes mellitus; however, this was much more obvious in those with no history of CVD. During the month of Ramadan, there were lower rates of admission with CHF while admissions with IHD were higher compared to the previous or following month in diabetic patients.
Keywords: diabetes; cardiovascular events; Ramadan; congestive heart failure; Ischemic heart disease